#TITLE_ALTERNATIVE# - BERYLIAN (NIM : 12213016, FADHIL
Some wells are not capable to reach Minimum Miscibility Pressure (MMP) in order to allow miscible CO2 injection, especially those with high temperature and depleted reservoir pressure. For these wells to reach MMP, reservoir pressure must exceed formation fracture pressure. A lot of additives have been added to injected stream to lower the MMP value, with varying results. This paper presents evaluation results of a different method to lower the MMP – using simple organic compounds. Twenty one different organic compounds from seven of the commonly known functional groups have been selected to be studied using WINPROP simulator version 2015, an EOS-based simulator. Nine compounds showing good performances are evaluated further using four different PVT samples at temperature of 150-300°F to examine their behavior towards change in oil composition and temperature. It is found that each compound has its own “optimum temperature” of reducing MMP. Ethylamine, Diethyl Ether, Propyl Amine, and Ethanol are the best choice of organic compounds, depending on reservoir temperature. A decrease of MMP up to 28% can be achieved by just adding 10 mole percent of organic compound into the injection stream. Results obtained from this study can be refined in further researches for use in field implementations.